Developing physical fitness through the principle of ‘repetition without repetition’ - Khubbiev, Sh.Z.; Zarodnyuk, G.V.; Karavan, A.V.; Zinoviev, N.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate ‘repetition without repetition’ as a principle for developing physical fitness. Methods and structure of the study. The study involved a review of the scientific and methodological literature, systematic analysis, deduction and induction, and content analysis. The research was conducted between 2024 and 2025. Results and conclusions. It has been established that the principle of ‘repetition without repetition’ refers to the repeated execution of movements to solve a motor task during the development of physical fitness. The latter is based on motor abilities.